A Panoramic Sketch about the Robust Stability of Time-Delay Systems and Its Applications. (27th September 2020) - Aguirre-Hernández, Baltazar; Villafuerte-Segura, Raúl; Luviano-Juárez, Alberto; Loredo-Villalobos, Carlos Arturo; Díaz-González, Edgar Cristian
Abstract : This paper presents a brief review on the current applications and perspectives on the stability of complex dynamical systems, with an emphasis on three main classes of systems such as delay-free systems, time-delay systems, and systems with uncertainties in its parameters, which lead to some criteria with necessary and/or sufficient conditions to determine stability and/or stabilization in the domains of frequency and time. Besides, criteria on robust stability and stability of nonlinear time-delay systems are presented, including some numerical approaches.